Мито як засіб регулювання зовнішньоекономічної діяльності України - Бондаренко, Валентин Юрійович; Bondarenko, Valentyn Yuriyovych (Ірпінь, 2024)
У ході роботи було розкрито суть аналізу теоретико-методологічних основ та практики реалізації митно-тарифного регулювання зовнішньоекономічної діяльності, визначення проблем та розробку шляхів вдосконалення механізму митного регулювання для створення сприятливих умов подальшого розвитку зовнішньоекономічної діяльності України

In the course of the work, the essence of the analysis of the theoretical and methodological foundations and practice of the implementation of customs and tariff regulation of foreign economic activity, the identification of problems and the development of ways to improve the mechanism of customs regulation in order to create favorable conditions for the further development of foreign economic activity of Ukraine were revealed
Customs duty as a means of regulating Ukraine’s foreign economic activity
Keywords: експорт; зовнішньоекономічна діяльність; імпорт; мито; митне регулювання; митно-тарифна система; export; foreign economic activity; import; customs duty; customs regulation; customs tariff system